Mixed-mobility supported lipid bilayers uncover the role of immobilized ICAM1 on T cell activation and immune synapse organization - Alexander Leithner; Audun Kvalvaag; Tanmay Mitra; Salvatore Valvo; Hannah Dada; Ewoud Compeer; Michael I. Barton; Sofia Bustamante Eguiguren; Edward Jenkins; Christoffer Lagerholm; Omer Dushek; Michael L. Dustin (Proceedings of the National Academy of Sciences, 2026)
The immunological synapse (IS) integrates antigen recognition and adhesion to control T cell activation and effector functions. Reductionist systems have been instrumental in dissecting IS organization, but conventional systems constrain all ligands to be either mobile or immobile, unlike antigen-presenting cells where intercellular adhesion molecule 1 (ICAM1) is cytoskeletally anchored while T cell receptor (TCR) ligands remain mobile. Here, we establish mixed-mobility supported lipid bilayers (SLBs) that simultaneously present mobile TCR agonists and immobile ICAM1. Selective immobilization of ICAM1 disrupts centripetal F-actin flow, prevents centralization of TCR microclusters and shifts signaling to peripheral microclusters. This attenuates TCR downregulation through ectocytosis while maintaining recycling, and enhances integrin mechanotransduction, reflected in increased phosphorylation of Focal Adhesion Kinase, Paxillin, and the stretch-sensitive adaptor CasL. Functionally, immobilized ICAM1 augments T cell activation, degranulation, Perforin release, and cytotoxicity. Importantly, these findings were recapitulated in a cell–cell system engineered to express either full-length, cytoskeleton-anchored ICAM1 or a truncated form lacking cytoskeletal association, with full-length ICAM1 consistently promoting stronger effector responses. These findings identify ligand mobility as a key biophysical parameter that shapes IS organization and T cell effector responses and establish mixed-mobility SLBs as a powerful tool for probing receptor mechanics in immunity.